2012
DOI: 10.3109/08880018.2012.676721
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyosarcoma Treatment and Outcome at a Multidisciplinary Pediatric Cancer Center in Lebanon

Abstract: Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma in children. Outcome of patients treated on standard protocols, in a multidisciplinary cancer center setting outside of clinical trials, is not well reported. We reviewed characteristics and outcome of 23 pediatric patients treated at a single, multidisciplinary cancer center in Lebanon, between April 2002 and December 2010. Median follow-up was 41 months. The most commonly affected primary site was the head and neck (48%, n = 11). Nineteen tumors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…RMS in children can originate from any site of body. Some researchers have showed that the head and neck region is the most common primary site in children with RMS, which accounts for 45%, while the primary site in the orbit accounts for 25-35% of patients with RMS in the head and neck region (Turner and Richmon, 2011;Badr et al, 2012;Salman et al, 2012). In this study, the most frequent positions in patients with RMS were in the orbit and eyelid, which accounted for 56.09% (23/41).…”
Section: Discussionmentioning
confidence: 70%
“…RMS in children can originate from any site of body. Some researchers have showed that the head and neck region is the most common primary site in children with RMS, which accounts for 45%, while the primary site in the orbit accounts for 25-35% of patients with RMS in the head and neck region (Turner and Richmon, 2011;Badr et al, 2012;Salman et al, 2012). In this study, the most frequent positions in patients with RMS were in the orbit and eyelid, which accounted for 56.09% (23/41).…”
Section: Discussionmentioning
confidence: 70%
“…This study reports 5-year overall and disease-free survival rates of 83% and 64%, respectively, which are impressive [1].…”
Section: To the Editormentioning
confidence: 70%
“…This study reports 5-year overall and disease-free survival rates of 83% and 64%, respectively, which are impressive [1].It is challenging to treat children with cancer in the developing world especially when multimodality care is needed. Treatment abandonment is a significant challenge in India due to multiple and complex social issues [2].…”
mentioning
confidence: 78%
“…Gatta G et al's review of rhabdomyosarcoma results in approximately 67% 5-years survival with multimodality therapy [28]. Rhabdomyosarcoma event-free survival (EFS) been reported lately were incentive [29,30]. Ma X, et al retrospective multicenter study results in 10 years EFS of 53.4 ± 5.1% [31].…”
Section: Discussionmentioning
confidence: 99%